Inherited Platelet Disorders: A Short Introduction - Zieger, Barbara; Boeckelmann, Doris (Hämostaseologie, 2023)
Platelets play an important role regarding coagulation by contributing to thrombus formation by platelet adhesion, aggregation, and α-/δ-granule secretion. Inherited platelet disorders (IPDs) are a very heterogeneous group of disorders that are phenotypically and biochemically diverse. Platelet dysfunction (thrombocytopathy) can be accompanied by a reduction in the number of thrombocytes (thrombocytopenia). The extent of the bleeding tendency can vary greatly. Symptoms comprise mucocutaneous bleeding (petechiae, gastrointestinal bleeding and/or menorrhagia, epistaxis) and increased hematoma tendency. Life-threatening bleeding can occur after trauma or surgery. In the last years, next-generation sequencing had a great impact on unrevealing the underlying genetic cause of individual IPDs. Because IPDs are so diverse, a comprehensive analysis of platelet function and genetic testing is indispensable.
Keywords: inherited platelet disorders; next-generation sequencing; Hermansky-Pudlak syndrome; GNE